Voriconazole Concentrations in Plasma and Epithelial Lining Fluid after Inhalation and Oral Treatment. Issue 5 (10th July 2017) - Andersen, Charlotte U.; Sønderskov, Lene Dahl; Bendstrup, Elisabeth; Voldby, Nina; Cass, Lindsey; Ayrton, John; Hilberg, Ole
Abstract: Adverse effects can compromise oral voriconazole treatment of pulmonary aspergillosis. Inhaled low‐dose voriconazole may be an alternative treatment. In this study, six patients inhaled 40 mg voriconazole b.i.d. for 2 days, and six patients ingested 400 and 200 mg orally b.i.d. on day one and two, respectively. Blood samples were collected after the first inhalation, and bronchial alveolar lavage fluids and blood samples were collected for measurements of voriconazole 12 hr after the last administration. The concentration of voriconazole in epithelial lining fluid (ELF) was calculated by the urea dilution method. Voriconazole concentrations were detectable in plasma 15 min. after inhalation and declined at 30 and 60 min. Twelve hours after the last dose, median (95% CI) plasma voriconazole concentration was 8 (4–26) ng/mL in the inhalation group and 1224 (535–2341) ng/mL in the oral group ( p < 0.0001). In ELF, median concentration was 190 (55–318) ng/mL and 8827 (4369–35172) ng/mL, respectively ( p < 0.0001). Median ELF/plasma concentration ratio was 21 (6–63) in the inhalation group and 8 (3–20) in the oral group ( p = 0.2). In conclusion, voriconazole is rapidly absorbed into the systemic circulation after inhalation. There was a non‐significant trend towards a higher ELF/plasma concentration ratio in the inhalation group compared to the oral group.